2007
DOI: 10.1007/s10509-007-9488-6
|View full text |Cite
|
Sign up to set email alerts
|

Energy and momentum distributions of Kantowski and Sachs space–time

Abstract: We use the Einstein, Bergmann-Thomson, Landau-Lifshitz and Papapetrou energy-momentum complexes to calculate the energy and momentum distributions of Kantowski and Sachs space-time. We show that the Einstein and Bergmann-Thomson definitions furnish a consistent result for the energy distribution, but the definition of LandauLifshitz do not agree with them. We show that a signature switch should affect about everything including energy distribution in the case of Einstein and Papapetrou prescriptions but not in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 44 publications
0
3
3
Order By: Relevance
“…For the space-time under consideration, we have found that the energy-momentum complexes of Einstein and BergmannThomson give the same results, while Landau-Lifshitz do not give the same results and do not concur with the aforementioned complexes. Moreover, the results obtained in this paper do not concur with the results obtained obviously in general relativity (Gad and Fouad 2007), using these different energy-momentum complexes.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…For the space-time under consideration, we have found that the energy-momentum complexes of Einstein and BergmannThomson give the same results, while Landau-Lifshitz do not give the same results and do not concur with the aforementioned complexes. Moreover, the results obtained in this paper do not concur with the results obtained obviously in general relativity (Gad and Fouad 2007), using these different energy-momentum complexes.…”
Section: Discussioncontrasting
confidence: 99%
“…These results do not concur with the results obtained in general relativity by using these different energy-momentum complexes (Gad and Fouad 2007).…”
Section: Energy and Momentum Associated With The Metric Of Kantowski-contrasting
confidence: 94%
“…In four-dimensions space-time, numerous works on evaluating the energy and momentum distributions using different complexes have been completed. For examples, Virbhadra [14][15][16][17][18][19][20], Virbhadra and his collaborators [21][22][23][24], Sharif [25][26][27][28], Ragab [29][30][31], and others [32][33][34][35][36][37][38][39] and found some a e-mail: faizuddinahmed15@gamil.com encouraging results. Aguirregabiria et al [40] showed that for any Kerr-Schild class metric, several energy-momentum complexes give the same results.…”
Section: Introductionmentioning
confidence: 99%
“…The energy density for the space-time under consideration, in the Cartesian coordinates, obtained in [10] is 6) and the total energy is…”
Section: On the Fourth Component Of Einstein's Complexmentioning
confidence: 99%
“…In a recent paper [10], Gad and Fouad have found the energy and momentum distribution of Kantowaski-Scahs space-time, using Einstein, Bergmann-Thomson, Landau-Lifshitz and Papapetrou energy momentum complexes. In this section we restrict our attention to the Einstein's complex which is defined by [11]…”
Section: On the Fourth Component Of Einstein's Complexmentioning
confidence: 99%